Maxillary Mucocele with Orbital Floor Remodelling - Tahrina Salam; Maryam Zamani; Jane Olver (Case Reports in Ophthalmological Medicine)
A 79-year-old man presents with signs of an orbital mass. A CT scan revealed a large maxillary mucocele eroding through the orbital floor. Surgical drainage of the mucocele and conservative postoperative care, returned all ophthalmic signs to normal and bony remodelling of the orbital floor was demonstrated. Maxillary mucoceles should be assessed by both ENT and Ophthalmic surgeons. Postoperative remodelling of the orbital floor can be illustrated with serial CT Scans.